Traditional threads: Kovai Kora cotton saree - Kanimozhi; Rajalakshmi
Tamil Nadu boasts a rich cultural heritage that has developed over the years. Tamil Nadu's handicrafts and handcrafted clothing are arguably the most abundant expression of Tamil culture. Saree is considered to be an asset in Indian women$1 (Bs life and it speaks about the art and culture. In Tamil Nadu, sarees show intricate design with unique characteristics Tamil Nadu sarees are distinctive in their cultural significance, designs, and weaving techniques. The cultural identity has been preserved through the generations-long transmission of weaving techniques and patterns. These sarees plays a major role in weddings, Festivals like Pongal and Temple rituals, symbolizing purity and prosperity. Sarees like Kanjeevaram sarees are a staple for weddings and auspicious occasions, Chettinad cotton sarees represent traditional south Indian Aesthetics, Madurai Sungudi sarees for casual and festive occasions, Kodambakkam silk Sarees bridge the tradition with modern fashion Trend, Kovai Kora cotton valued for their comfort touch of tradition. This review articles deals with the historical origin, geographical indication, product specification, production process and uniqueness of Kovai Kora cotton saree.s